The Effect of Progressive Muscle Relaxation on Blood Pressure Reduction as An Effort to Prevent Emergencies in Hypertensive Patients - Risdiana Melinda Naibaho; Rugun Togianur Lingga (Universitas Islam Negeri Sumatera Utara, Medan, 2024)
Hypertension, which is characterized by an increase in blood pressure above normal limits, is a health problem that can occur in all walks of life. People with hypertension are often unaware of this condition because it generally does not show obvious symptoms. If left untreated, hypertension can cause irreversible damage to the arteries, increase the risk of cardiovascular disease, and can lead to hypertensive emergencies. Hypertension can be prevented and managed with proper treatment, which can reduce the risk of serious complications such as stroke and heart attack. Progressive muscle relaxation is one of the non-pharmacological therapies that can be used to lower blood pressure. This technique combines deep breathing exercises, systematic contraction and relaxation of the body's muscle groups to help relieve physical and psychological tension. By reducing stress and muscle tension, and stimulating the nervous system to function more efficiently in regulating body functions related to blood pressure, a significant reduction in blood pressure is expected. This study aims to evaluate the effectiveness of progressive muscle relaxation techniques in reducing blood pressure in hypertensive patients as an effort to prevent hypertension emergencies. The method used was a pre-experimental design with a One Group Pretest-Posttest design. The research sample consisted of 66 respondents who participated in progressive muscle relaxation sessions. The results of data analysis showed a decrease in mean systolic blood pressure by 12.21 mmHg and diastolic by 10.96 mmHg. Statistical tests using Paired Sample t-test showed a p value <0.01, which indicates a significant difference at the 95% level of significance (α = 0.05). These findings indicate that progressive muscle relaxation is effective in reducing blood pressure in hypertensive patients and can be one of the efforts to prevent hypertensive emergencies.Keywords: Blood pressure, Progressive muscle relaxation, Prevention of hypertensive emergencies